Specificity of the bilingual advantage for memory: examining cued recall, generalization, and working memory in monolingual, bilingual, and trilingual toddlers - Brito, Natalie H.; Grenell, Amanda; Barr, Rachel (Frontiers in Psychology, 2014)
The specificity of the bilingual advantage in memory was examined by testing groups of monolingual, bilingual, and trilingual 24-month-olds on tasks tapping cued recall, memory generalization and working memory. For the cued recall and memory generalization conditions, there was a 24-hour delay between time of encoding and time of retrieval. In addition to the memory tasks, parent-toddler dyads completed a picture-book reading task, in order to observe emotional responsiveness, and a parental report of productive vocabulary. Results indicated no difference between language groups on cued recall, working memory, emotional responsiveness, or productive vocabulary, but a significant difference was found in the memory generalization condition with only the bilingual group outperforming the baseline control group. These results replicate and extend results from past studies (Brito and Barr, 2012; 2014; Brito et al., in press) and suggest a bilingual advantage specific to memory generalization.